Pengaruh Pemberian Mata Kuliah Perpajakan, Pelatihan Brevet Pajak dan Pertimbangan Pasar Kerja Terhadap Minat Mahasiswa Berkarir di Bidang Perpajakan - Lutfiansyah, Lutfiansyah; Handayani, Henni Rahayu (JURNAL AKUNTANSI BARELANG, 2024)
The purpose of this study is to analyze the influence of the Provision of Tax Courses, Tax Brevet Training and Job Market Considerations on Student Interest in Career in the Field of Taxation. This type of research is a quantitative research with primary data sources. The population in this study is Pamulang University students with the Accounting Study Program and have or are taking Brevet. The sample selection method used in this study is purposive sampling so that the final sample obtained is 80 students. Testing the data quality using validity and reliability tests using IBM SPSS25 software, the next step is to test the classic assumptions, namely the normality test, the multicollinearity test and the hexaoscedasticity test after that the hypothesis test. From the results that have been carried out in this study, it shows that Taxation Courses, Tax Brevet Training and Job Market Considerations simultaneously affect the Interest of Students in Career in the Field of Taxation. Partially shows that the Taxation and Market Consideration Course has an effect on the Interest of Career Students in the Field of Taxation. Meanwhile, the Tax Brevet Training partially has no effect on the interest of students in a career in taxation in students of the University of Pamulang Accounting Study Program.